Comparative Analysis of Judicial Statistics Reform: Insights From The US, Canada, and The UK - Sally Sophia; Salma Zahra; Akmal Azizan; Nurajam Perai (Jurnal Hukum dan Peradilan, 2025)
In the context of modern judiciaries, the effective utilization of judicial statistics is pivotal for informed decision-making and policy formulation. Indonesia, like many nations, faces challenges in the dissemination, content coherence, raw data sharing, historical analysis, and collaborative efforts concerning judicial statistics. This research addresses these gaps by proposing innovative solutions to enhance the efficacy of judicial statistics in Indonesia. The primary objective is to transform the existing landscape by advocating for the adoption of web-based platforms, restructuring content and format, resolving raw data dissemination challenges, emphasizing the significance of historical data, and promoting collaborative efforts between research institutions and court data centers. The purpose is to provide a comprehensive framework that not only addresses current issues but also lays the foundation for sustainable, transparent, and informed statistical practices. This study employs a qualitative approach through a comparative analysis, examining existing literature, policy documents, and judicial statistics practices in the US, Canada, and the UK. By contrasting these systems with Indonesia’s framework, the study identifies best practices and potential improvements for judicial data management. The research presents a multifaceted approach to enhance the efficacy of judicial statistics in Indonesia. By transitioning to web-based platforms, ensuring content coherence, addressing raw data dissemination challenges, emphasizing historical data analysis, and promoting collaborative efforts, the proposed framework offers practical solutions. Implementation of these strategies can significantly improve the accessibility, accuracy, and relevance of judicial statistics. Consequently, this approach not only benefits researchers and policymakers but also fosters transparency and accountability within the Indonesian judiciary, paving the way for evidence-based decision-making and informed policy formulation in the legal sector.